Socio-digital interests, networks and excessive ICT engagement in Finnish adolescents - Kruskopf, Milla (fi=Turun yliopisto|en=University of Turku|, 2016)
The rise of modern socio-digital technologies has fundamentally changed the ways in which people communicate, cultivate interests and simply live their everyday lives in the new media ecology. This study sheds some light on Southern Finnish adolescents (N=17) socio-digital interests, networks and excessive ICT engagement based on mixed, self-report methods of theme interview, self-report questionnaire and social network questionnaire. During the interviews, the participants were also requested to reflect on their interest related egocentric networks or key-events in their interests development by means of drawing. The results indicated, that there were clear differences in the primary interests’ development and the networks related to it, and also in the experiences of the excessiveness of ICT use between the three profiles of socio-digital participation or interests: the basic, non-digital interest group, the creative digital media interest group and the digital gaming oriented interest group derived from a previously conducted self-report questionnaire. Also the youth in general appeared to experience their ICT use as excessive to some degree, but present criticism towards the concept of “ICT addiction” as well.

Modernien sosiodigitaalisen teknologioiden nousu on perusteellisesti muuttanut ihmisten kommunikaation, harrastamisen ja yksinkertaisesti jokapäiväisen elämisen tapoja nykyisessä uusmediaekologiassa. Tämä tutkimus valaisee hieman eteläsuomalaisten nuorten (N=71) sosiodigitaalisia kiinnostuksia, verkostoja ja liiallista TVT-sitoutuneisuutta perustuen teemahaastattelu-, kysely- ja verkostokyselyaineistoihin. Haastattelujen aikana osallistujia pyydettiin myös pohtimaan kiinnostuksiinsa liittyviä egosentrisiä sosiaalisia verkostoja tai sen kehitykseen liittyviä avaintapahtumia piirustuksen avulla. Tulokset viittaavat siihen, että primäärikiinnostuksen kehityksessä, siihen liittyvissä verkostoissa ja liiallisessa ICT-sitoutuneisuudessa on selviä eroja kolmen, aiemman kyselytutkimuksen perusteella muodostetun sosiodigitaalisen kiinnostuksen tai osallistumisen ryhmän välillä: ei-digitaalisen kiinnostuksen ryhmän, luovan, digitaalisen median kiinnostuksen ryhmän ja digitaaliseen pelaamiseen suuntautuneen ryhmän. Nuoret myös arvioivat yleisesti ICT:n käyttönsä jossain määrin liialliseksi, mutta esittivät myös kritiikkiä ”ICT-addiktion” käsitettä kohtaan.